Facile Fabrication of Bio‐ and Dual‐Functional Poly(2‐oxazoline) Bottle‐Brush Brush Surfaces. Issue 12 (12th February 2020) - Du, Yunhao; Zhang, Tao; Gieseler, Dan; Schneider, Maximilian; Hafner, Daniel; Sheng, Wenbo; Li, Wei; Lange, Fred; Wegener, Erik; Amin, Ihsan; Jordan, Rainer
Abstract: Poly(2‐oxazoline)s (POx) bottle‐brush brushes have excellent biocompatible and lubricious properties, which are promising for the functionalization of surfaces for biomedical devices. Herein, a facile synthesis of POx is reported which is based bottle‐brush brushes (BBBs) on solid substrates. Initially, backbone brushes of poly(2‐isopropenyl‐2‐oxazoline) (PIPOx) were fabricated via surface initiated Cu 0 plate‐mediated controlled radical polymerization (SI‐Cu 0 CRP). Poly(2‐methyl‐2‐oxazoline) (PMeOx) side chains were subsequently grafted from the PIPOx backbone via living cationic ring opening polymerization (LCROP), which result in ≈100 % increase in brush thickness (from 58 to 110 nm). The resultant BBBs shows tunable thickness up to 300 nm and high grafting density ( σ ) with 0.42 chains nm −2 . The synthetic procedure of POx BBBs can be further simplified by using SI‐Cu 0 CRP with POx molecular brush as macromonomer ( M n =536 g mol −1, PDI=1.10), which results in BBBs surface up to 60 nm with well‐defined molecular structure. Both procedures are significantly superior to the state‐of‐art approaches for the synthesis of POx BBBs, which are promising to design bio‐functional surfaces. Abstract : The facile fabrication of POx BBBs with high layer thickness (up to ≈300 nm) and grafting density ( σ =0.42 chains nm −2 ) via surface‐initiated Cu‐mediated controlled radical polymerization (SI‐Cu 0 CRP) is presented. The patterned and gradient POx BBB surfaces were fabricated in a straightforward manner. The dual functionalities of POx BBBs were demonstrated by fluorescent labelling.